2014
DOI: 10.1037/a0033408
|View full text |Cite
|
Sign up to set email alerts
|

Emotional responses during reading: Physiological responses predict real-time reading comprehension.

Abstract: This study investigated the relationship between emotional responses and reading performance in middle-school students. Although a large number of prior studies have investigated the relationship between emotion and reading, those studies have concentrated primarily on relatively static and distal measures of emotion. In this research, we measured 7th-and 8th-grade students' (n = 44) emotional responses more proximally: during the reading tasks themselves. To do this, we used a cardiovascular indicator, respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 54 publications
3
26
0
1
Order By: Relevance
“…We recommend that future research include process measures for these constructs, evinced in eye tracking, concurrent verbalizations, or reading times, which in turn could be instructionally scaffolded (Poitras & Trevors, 2012) and analyzed with mixed-method research design (Trevors, Feyzi-Behnagh, Azevedo, & Bouchet, 2016). Likewise, self-reported measurement of valence categories of emotion (e.g., negative emotions) can be complemented by additional analysis of discrete emotions (e.g., anxiety, confusion) and physiological measures, such as analysis of electrocardiograms or facial expressions (Daley, Willet, & Fischer, 2014;.…”
Section: Limitations and Future Directionsmentioning
confidence: 98%
“…We recommend that future research include process measures for these constructs, evinced in eye tracking, concurrent verbalizations, or reading times, which in turn could be instructionally scaffolded (Poitras & Trevors, 2012) and analyzed with mixed-method research design (Trevors, Feyzi-Behnagh, Azevedo, & Bouchet, 2016). Likewise, self-reported measurement of valence categories of emotion (e.g., negative emotions) can be complemented by additional analysis of discrete emotions (e.g., anxiety, confusion) and physiological measures, such as analysis of electrocardiograms or facial expressions (Daley, Willet, & Fischer, 2014;.…”
Section: Limitations and Future Directionsmentioning
confidence: 98%
“…Dynamic and simultaneous physiological measures provide a unique framework for understanding emotion and cognition that cannot be provided by static measures like self-reports (Daley, Willett, & Fischer, 2014). Dynamic and simultaneous physiological measures provide a unique framework for understanding emotion and cognition that cannot be provided by static measures like self-reports (Daley, Willett, & Fischer, 2014).…”
Section: Arousal As a Physiological Measure Of Anxietymentioning
confidence: 99%
“…For instance, Everatt and Brannan (1996) gave students with RD and non-RD a spelling test either before or after a non-verbal task. Recently, Daley et al (2014) used a cardiovascular measure during a reading comprehension task. Everatt and Brannan suggested that the most plausible explanation for this was that the stress and anxiety caused by the spelling task carried over to the other tasks and impaired performance.…”
Section: Potential Links Between Anxiety and Reading Disabilitymentioning
confidence: 99%
See 2 more Smart Citations